Internal Factors Within an Auditor Influence the Quality of the Audit - Aldya Rizky Maulana; Magda Siahaan; Theonino David Nauli (Journal of International Accounting, Taxation and Information Systems, 2024)
This research aims to obtain empirical evidence about the influence of independence, professionalism, professional scepticism, competence, experience, and auditor integrity on audit quality. The object of this research is a public accountant who works as an auditor. The sample used in this research was 64 respondents. The data in this research was obtained using a questionnaire distributed to public accountants who were willing to provide answers. The results of this research show that independence, professionalism, and professional scepticism have no effect on audit quality, and competence, experience, and auditor integrity have a positive effect on audit quality. That is because independence, professionalism, and professional scepticism are elements that are automatically inherent in an auditor when carrying out their duties, so they do not affect the quality of the auditor's audit; apart from these three factors, other factors greatly influence the quality of the auditor.